Zapsolver: um bot direcionado ao ensino aprendizagem de Matemática - SOUZA, Camila Mayara Cardoso de (2022)
Although the contact with digital technologies is altogether present in our daily lives, we still face on to the challenges in associating pedagogical content in schools. With the worsening of the Covid-19 pandemic, we highlight the commitment of teaching. This reinforces the idea that it is important to seek necessary techniques for meaningful learning. On the other hand, social isolation led us to a series of Digital, Informational and Communication Technological Adaptations (TDIC). The need for the study arises from the relevance of repairing the impacts on the educational process, using a mediating technological resource. This project aims to present a ChatBot application, responsible for creating algebraic resolutions, intended to help elementary school students. The study methodologies are qualitative and quantitative, with an exploratory focus, aiming to improve the performance of studies in online classes. We note that a Chatbot has multiple pedagogical assistance functions, such as content review, exercise practice and offers interdisciplinary support.